Optimization of MQL-Turning Process Parameters to Produce Environmentally-Benign AISI 4340 Alloy with Nano-Lubricants using Cuckoo Search Algorithm - Ozule, Chukwuka Prosper; Oke, Sunday Ayoola; Rajan, John; Nwankiti, Ugochukwu Sixtus; Jose, Swaminathan; Oyetunji, Elkanah Olaosebikan; Adedeji, Kasali Aderinmoye (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
The current research consists of a machining process involving AISI steel where the input parameters are the cutting depth, feed rate and cutting speed while the responses include the cutting force, surface roughness and tool wear. Usually, heat is generated during the turning process and various machining processes, and to reduce it, coolants are considered. In this work, CuO and Al2O3 were used as nano lubricants (MQL). Data obtained from the machining process were inserted into Minitab 18 software where quadratic objective functions were formulated as related to each output concerning the input parameters. Objective functions were optimized with the aid of C++ programming code. The cuckoo search algorithm was used for the optimization process of the work. This work clearly shows a reduction of the output parameters that is, cutting force from 243N to 127.20N, surface roughness from 0.66µm to 0.368µm and tool wear from 0.069mm to 0.0046mm using CuO as the nano lubricant. While using Al2O3, cutting force was lowered from 363N to 197.63N, surface roughness from 1.98µm to 0.148µm and tool wear from 0.219mm to 0.063mm. This clearly shows that using CuO helps to obtain a better cutting force coupled with elongation of the tool life but Al2O3 best gives a better surface finish.